Mixed Context Based Teaching: A Student Centric Pedagogy to Teach Physical Science in High School Classroom (Unnes Science Education Journal, 2022)
The purpose of this study is to investgate mixed content based teaching using a student centric pedagogy to teach physical science in high school classroom. Mixed Context Based Teaching (MCBT) was developed as an alternative pedagogy. MCBT in Grade 10 classrooms was investigated in the Nkomazi municipal region of South Africa’s Mpumalanga province. Despite a lack of resources at the school, MCBT was found to increase Chemistry teaching learning outcomes. In this study MCBT was used to teach chemistry content of physical science. The developed pedagogy uses a controlled dialogic method combined with context and analogy to teach. Present study used a mixed method of data analysis. Pre-testing and post-testing was used in this quasi-experimental investigation. In this study, quantitative data was collected and used for finding the answer for the research questions even though we used an exploratory sequential mixed-method research design. There were two distinct groups. A control group and an experimental group were created. A control group consisted 31 students and an experimental group had 50 students. Pre-test and pot-test data were collected from control group as well from experimental group. It also included four in-service teachers as co-researchers. They assisted in the administration of pre-tests and post-tests, as well as observing the class delivery process. Teachers who took part in the study returned to their schools and incorporated MCBT in their classes. The lead researcher watched the participating teachers’ lessons using a refined teaching observation procedure. After working on MCBT deployment in classrooms, these teachers provided a collection of qualitative data. An analysis of quantitative data using z-stats, showed statistically significant differences in the performances between control and experimental groups. The study found that a hybrid context-based pedagogy was beneficial in enhancing Chemistry teaching and learning results in rural schools with limited resources. Any technology-based teaching technique could be costly, however MCBT has no financial costs other than the training of participating teachers. The observations of this study opens an opportunity to adopt an improved teaching-learning method for underdeveloped and developing countries’ rural poor country sides, where finances are a barrier to enhancing Chemistry teaching-learning outcomes.